Analytical methods for mercury speciation in several matrixes: a review - Ramalhosa, Elsa (2011)
Mercury is one of the hazardous contaminants that may be present in the environment. Moreover, its toxicological effects are strongly dependent on the chemical form of the element, being the organic species the most toxic. In spite of this, the determination of mercury compounds in environmental samples, such as water, soils, sediments and biological matrixes, is of great importance. This review examines the current state of the sample treatments that have been developed, during the last 18 years (1990-2007),previous to separation and detection of mercury compounds, namely acid lixiviation, distillation,alkaline digestion and supercritical fluid extraction, as well as of the chromatographic techniques (gas chromatography and high performance liquid chromatography) used in order to separate mercury compounds and detection techniques usually coupled with them. The detection limits and the linear range achieved coupling both separation techniques with different detectors are presented, as well as the advantages and disadvantages of each one. Finally, a brief discussion over the most used detection systems is also presented.